ANALISIS IMPLEMENTASI PENDEKATAN SAINTIFIK DALAM PEMBELAJARAN ANAK USIA DINI DI PAUD AMRINA SUNGAI PINANG - Putri Monica, Farah; Hamzah, Amir; Muhtarom (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the importance of early childhood education as the foundation for children’s cognitive, social-emotional, language, and physical development during the golden age period. A scientific approach is considered relevant in early childhood learning because it emphasizes observing, questioning, experimenting, reasoning, and communicating in constructing knowledge through direct experiences. However, its implementation in early childhood education institutions still faces several challenges, including limited facilities, an imbalance between the number of teachers and students, and varying levels of teachers’ understanding of the approach. This research aims to analyze the implementation of the scientific approach in early childhood learning at PAUD Amrina Sungai Pinang and to identify its supporting and inhibiting factors. The study employed a qualitative descriptive method. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, data display, and conclusion drawing. The findings reveal that the scientific approach has been implemented through exploratory activities such as observation, simple experiments, discussions, and presentations, although it has not yet been fully optimized. Supporting factors include teachers’ commitment and institutional support, while inhibiting factors involve limited facilities, time constraints, and the limited number of educators. Efforts to overcome these challenges include utilizing the surrounding environment as a learning resource and enhancing teachers’ creativity in designing learning activities. The study concludes that the scientific approach has significant potential to improve the quality of early childhood learning when supported by adequate teacher competence and facilities.